2015
DOI: 10.1126/science.aaa5397
|View full text |Cite
|
Sign up to set email alerts
|

Quasar quartet embedded in giant nebula reveals rare massive structure in distant universe

Abstract: All galaxies once passed through a hyperluminous quasar phase powered by accretion onto a supermassive black hole. But because these episodes are brief, quasars are rare objects typically separated by cosmological distances. In a survey for Lyman-α emission at redshift z ≈ 2, we discovered a physical association of four quasars embedded in a giant nebula. Located within a substantial overdensity of galaxies, this system is probably the progenitor of a massive galaxy cluster. The chance probability of finding a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
349
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 246 publications
(372 citation statements)
references
References 123 publications
20
349
2
1
Order By: Relevance
“…The three giant nebulae discovered hitherto with NB imaging (Cantalupo et al 2014;Martin et al 2014;Hennawi et al 2015) are all characterized by bright extended emission with surface brightness values larger than 10 −17 erg s −1 cm −2 arcsec −2 , a value that is easily reachable within 1 hr of integration time with MUSE. Therefore, for this exploratory survey (094.A-0396, 095.A-0708, 096.A-0345), we use a total exposure time of 1 hr for each quasar split into 4×900 s exposures.…”
Section: Observational Strategymentioning
confidence: 99%
See 4 more Smart Citations
“…The three giant nebulae discovered hitherto with NB imaging (Cantalupo et al 2014;Martin et al 2014;Hennawi et al 2015) are all characterized by bright extended emission with surface brightness values larger than 10 −17 erg s −1 cm −2 arcsec −2 , a value that is easily reachable within 1 hr of integration time with MUSE. Therefore, for this exploratory survey (094.A-0396, 095.A-0708, 096.A-0345), we use a total exposure time of 1 hr for each quasar split into 4×900 s exposures.…”
Section: Observational Strategymentioning
confidence: 99%
“…This result seems to be in stark contrast with previous narrow-band and spectroscopic surveys for bright radio-quiet quasars at highredshift. These studies have found detection rates of giant nebula less than 10% using NB imaging at < < z 2 3 (Cantalupo et al 2014;Martin et al 2014;Hennawi et al 2015;Arrigoni Battaia et al 2016), while spectroscopic surveys at any redshift have found exclusively smaller nebulae (<60 pkpc) and only in about 50% of the cases (North et al 2012;Fathivavsari et al 2015). Because all these surveys-including our MUSE observations-reached a similar depth, the origin of this discrepancy must be searched for somewhere else.…”
Section: Why Such a High Detection Ratementioning
confidence: 99%
See 3 more Smart Citations